Effect of larval density and surface area on development rates of aedes albopictus (Skuse) (Diptera: Culicidae) in polystyrene container / Nor Syahira Ahmad - Ahmad, Nor Syahira (2018)
Dengue is a threat to public health as the Aedes species are adapting to the changing ecology and it was found breeding in varies sorts of breeding containers over the times. Laboratory strains of Aedes albopictus were reared in control condition under different larval densities and surface area of polystyrene containers to compare their development in the immature and adult stage. This study found that the duration of fifty percent time to pupation of Ae. albopictus is between 6.00 to 10.00 days with shortest time in polystyrene container, C1 with 150 larvae/cm² at day 6.67. Meanwhile, the duration of adult emergence was the fastest in polystyrene container, C1 with 150 larvae/cm² at day 9.00 with averaged 9.0 to 12.00 days in other treatment. Two-Way ANOVA was used as the larval density significantly impacted the juvenile size and wing size. Polystyrene container, C1 was recorded as the smallest size with 150 larvae/cm²: 5.92 mm for juvenile size and 2.03 mm for wing size. As for the larval development between larval density and surface area containers, there is statistically significant (p < 0.05). In addition, the mortality rate of larval in the polystyrene container, C1 was recorded as the highest mortality rates (2 % to 3.78%). The data indicate that competition within larval environment may indirectly regulate Aedes populations by reducing body size, which may in turn reduce survivorship. Thus, this could act as a point in recognizing the pattern of Aedes reproduction to planning vector control measure in Malaysia.